2014
DOI: 10.1371/journal.pone.0101222
|View full text |Cite
|
Sign up to set email alerts
|

Aurora Kinase A Is Not Involved in CPEB1 Phosphorylation and cyclin B1 mRNA Polyadenylation during Meiotic Maturation of Porcine Oocytes

Abstract: Regulation of mRNA translation by cytoplasmic polyadenylation is known to be important for oocyte maturation and further development. This process is generally controlled by phosphorylation of cytoplasmic polyadenylation element binding protein 1 (CPEB1). The aim of this study is to determine the role of Aurora kinase A in CPEB1 phosphorylation and the consequent CPEB1-dependent polyadenylation of maternal mRNAs during mammalian oocyte meiosis. For this purpose, we specifically inhibited Aurora kinase A with M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 54 publications
1
22
2
Order By: Relevance
“…The CPEB2 protein was stable until metaphase I, when its partial degradation occurred. This matches with its paralog CPEB1, the degradation of which is necessary for the transition between metaphase I and metaphase II in Xenopus oocytes [ 19 ], and which has also been observed also in porcine oocytes [ 38 ]. Mendez et al [ 19 ] reported similar results, suggesting that the degradation of CPEB1 is necessary for the transition between metaphase I and metaphases II in Xenopus oocytes.…”
Section: Discussionsupporting
confidence: 67%
“…The CPEB2 protein was stable until metaphase I, when its partial degradation occurred. This matches with its paralog CPEB1, the degradation of which is necessary for the transition between metaphase I and metaphase II in Xenopus oocytes [ 19 ], and which has also been observed also in porcine oocytes [ 38 ]. Mendez et al [ 19 ] reported similar results, suggesting that the degradation of CPEB1 is necessary for the transition between metaphase I and metaphases II in Xenopus oocytes.…”
Section: Discussionsupporting
confidence: 67%
“…In contrast with mitotic cell cycles, this transition has not been reported to require cyclin A (Kobayashi et al, 1991;Minshull et al, 1991;Okano-Uchida et al, 1998;Nebreda and Ferby, 2000;Kishimoto, 2003Kishimoto, , 2018. Furthermore, Plk1 (Pahlavan et al, 2000;Okano-Uchida et al, 2003;Gaffré et al, 2011) and Aurora (Maton et al, 2003;Abe et al, 2010;Komrskova et al, 2014) are nonessential for transition in some oocytes. Thus, mechanisms other than the cyclin A-Cdk1/Plk1 axis likely trigger cyclin B-Cdk1 activation in oocytes.…”
Section: Introductionmentioning
confidence: 87%
“…The mechanisms of temporal and selective activation of maternal mRNAs are complicated and diverse among species (Komrskova et al, 2014). Cytoplasmic polyadenylation of the 3′-untranslated region (3′-UTR) is largely correlated with mRNA stability and translational activation of mRNA, and plays an essential role in oocyte maturation.…”
Section: Introductionmentioning
confidence: 99%